Pulmonary manifestations in Behçet disease: impaired natural killer cells activity - Hamzaoui, Kamel; Berraies, Anissa; Kaabachi, Wajih; Ammar, Jamel; Hamzaoui, Agnès (Multidisciplinary Respiratory Medicine, 2013)
Background: Behçet’s disease (BD) is a systemic vasculitis with unknown aetiology, where, besides genetic predisposition, an immune dysregulation involving T and B lymphocytes and hyperactive neutrophils contribute to disease pathogenesis. The aim of this study was to determine the cytotoxicity of natural killer (NK) cells in bronchoalveolar lavage (BAL) from BD patients with pulmonary manifestations. Methods: BAL was performed in 27 patients with BD and pulmonary manifestations, 14 patients with Rheumatoid Arthritis (RA) and 23 healthy controls (HC). Related orphan receptor C (RORC) and forkheadbox P3 (FOXP3) mRNA transcript were determined in BAL by reverse transcription–polymerase chain reaction (RT-PCR). NK cells, NK cell cytotoxicity, and lymphokine-activated killer (LAK) activity against K562 cells were measured by flow cytometry. Proportions of NK precursors and expression of genes for IL-2 receptor β (IL-2Rβ; CD122), perforin, and granzyme in NK cells were measured by flow cytometry or RT-PCR. Results: The analysis of transcription factors revealed an increase in the RORC/FOXP3 ratio (Th17/Treg cells) in BAL from BD patients. Percentages of NK were significantly lower in BD than in RA patients and healthy controls. Purified NK cells derived from BD patients were found to have lower cytotoxicity and LAK activity than those from controls. This defect of NK cells in BD patients was related to down-regulation of perforin and granzyme expression in NK cells. Conclusion: In BD patients, the increased RORC/FOXP3 ratio indicated an inflammatory state of the lung. NK cells were decreased together with an impairment of their activity due to a defective expression of granzyme and perforin. These abnormalities possibly contribute to immune system dysregulation found in BAL of BD patients with pulmonary manifestations.